The influence of social media usage and creativity on entrepreneurial intentions among Generation Z - Fitriyani, Atika Handa; Ahadiat, Ayi; Husna, Nurul (Lighthouse Publishing, 2025)
Generation Z is known as a generation that is adaptive to technology, including social media, which plays an important role in supporting the development of creative ideas in entrepreneurship. The use of social media allows individuals to obtain information, expand networks, and promote products or services effectively. In addition, creativity is one of the main abilities that drives individuals in creating opportunities and innovations in the business world. This study aims to analyze the effect of social media use and creativity on entrepreneurial intentions in Generation Z in Bandar Lampung. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 240 Generation Z respondents in Bandar Lampung. Data were analyzed using multiple regression statistical tests. The results of the study indicate that the use of social media has a positive and significant effect on entrepreneurial intentions in Generation Z in Bandar Lampung and creativity also has a positive and significant effect on entrepreneurial intentions in Generation Z in Bandar Lampung. Based on these findings, it is recommended for Generation Z to be more proactive in interacting with contacts who have the potential to provide entrepreneurial information and to be active in activities that stimulate creativity. In addition, it is important to increase motivation, understanding, and support to be more confident in setting entrepreneurial goals.